Daphnia depth selection in gradients of light intensity from different artificial sources: An evolutionary trap?. Issue 4 (29th January 2021) - Maszczyk, Piotr; Tałanda, Joanna; Babkiewicz, Ewa; Leniowski, Konrad; Urban, Paulina
Abstract: It is well known that artificial light at night alters the natural patterns of light in space and time, which interrupts a variety of physiological processes of individuals, altering their life history and behavioral adjustments. However, much less is known about the effect of artificial light at night on their fitness. We tested the hypothesis that planktonic animals, such as Daphnia spp., are able to correctly assess light intensity‐ and spectrum‐dependent‐mortality risk due to predation by planktivorous fish and select depths offering the highest possible fitness gain in the vertical gradient of different artificial light sources (halogen, metal‐halide, cool white LEDs, and high pressure sodium lamps) commonly used in street lighting. To test this hypothesis, we compared the virtual distributions of three clones of Daphnia longispina from simulations based on an experimentally parameterized, optimizing individual‐based model with distributions observed in laboratory experiments performed with 5‐d‐old individuals in an experimental apparatus comprised of twin vertical columns. Our hypothesis was confirmed only partially, since the distributions obtained in the experiments overlapped the virtual distributions only in the gradient of LEDs and high pressure sodium light, which suggests that that the strength of the maladaptive response could depend on the type of artificial light (i.e., spectral composition) penetrating the water column. Moreover, the results revealed that the response to the presence of artificial light is clone‐specific, which suggest that it could be a selective factor for microevolutionary changes.